INFLUENCE OF SUNSHINE (IN HOURS) ON THE DEVELOPMENT OF STROKES AMONG THE POPULATION IN SOUTHERN KYRGYZSTAN (American Journal of Pedagogical and Educational Research, 2023)
Acute cerebrovascular accidents (ACVA) occupy priority ranking positions in the structure of neurological pathologies. The differences and incidence of stroke may be due to climatic conditions that differ in different regions of Kyrgyzstan. The purpose of the study is to study the risk of developing cerebral stroke over 4 years under the influence of meteorological factors for the timely adoption of preventive measures.